Complex streamflow responses to climate warming in five river basins in South Yakutia, Russia - Wang, Ping; Shpakova, Raisa N. (Frontiers in Environmental Science, 2022)
The climate is warming much faster than the global average at the northern mid–high latitudes, leading to intensified hydrological cycles. However, it is unclear whether the response of streamflow to climate change is uniform across river basins with areas of 104 km2 to 105 km2. In this study, monthly streamflow data from five river basins (Bol'shoy Patom, Chara, Olekma, Timpton, and Uchur) and gridded monthly temperature and precipitation data from the Russian South Yakutia at 53.5-61.5°N were analysed to investigate changes in their annual streamflow from 1934 to 2019 and their responses to climate warming. The results showed significant increasing trends in air temperature for all five basins at rates of 0.20-0.22 °C/decade (p<0.001), with faster warming after the 1980s. Apart from the Uchur River Basin, increasing trends in annual precipitation were observed in the other four river basins at rates of 9.3-15.7 mm/decade (p<0.01). However, temporal changes in streamflow were much more complex than those in air temperature and precipitation among the five basins. Only two of the five basins showed significant increasing trends in annual streamflow with change rates of 17.1 mm/decade (p<0.001) for the Chara River and 7.7 mm/decade (p<0.05) for the Olekma River. Although the other three basins showed slightly increasing trends in annual streamflow (1.8-4.0 mm/decade), these trends did not pass significance tests (p>0.05). By analysing the temperature-precipitation-streamflow relationships, we determined that the annual streamflow positively responds to precipitation, while winter streamflow is most sensitive to temperature. With climate warming, the streamflow during the winter period (October-April) increased significantly in four of the five river basins at rates of 1.4-3.1 mm/decade (p<0.001), suggesting that warming-induced permafrost thawing increases baseflow. Although the streamflow response of large Siberian rivers to climate change is consistent, our results suggest that the streamflow response to climate change in relatively small river basins (104 km2 to 105 km2) is much more complex.